Molecular and Functional Analysis of Pore-Forming Toxin Monalysin From Entomopathogenic Bacterium Pseudomonas entomophila - Nonaka, Saori; Salim, Emil; Kamiya, Koki; Hori, Aki; Nainu, Firzan; Asri, Rangga Meidianto; Masyita, Ayu; Nishiuchi, Takumi; Takeuchi, Shoji; Kodera, Noriyuki; Kuraishi, Takayuki (Frontiers in Immunology, 2020)
Pseudomonas entomophila is a highly pathogenic bacterium that infects insects. It is also used as a suitable model pathogen to analyze Drosophila’s innate immunity. P. entomophila’s virulence is largely derived from Monalysin, a β-barrel pore-forming toxin that damages Drosophila tissues, inducing necrotic cell death. Here we report the first and efficient purification of endogenous Monalysin and its characterization. Monalysin is successfully purified as a pro-form, and trypsin treatment results in a cleaved mature form of purified Monalysin that kills Drosophila cell lines more effectively. Adult flies are susceptible to the injection of mature Monalysin, and humoral innate immunity is activated perhaps not by peptidoglycan, but tissue damage. Electrophysiological measurement of Monalysin in a lipid membrane with an on-chip device confirms that Monalysin forms a pore, in a cleavage-dependent manner, and provides a pore-size estimate of Monalysin using the current amplitude for a single pore. Atomic Force Microscope (AFM) analysis displays its structure in a solution and shows that active-Monalysin is stable and composed of an 8-mer complex; this observation is consistent with mass spectrometry data. AFM analysis also shows the 8-mer structure of active-Monalysin in a lipid bilayer, and real-time imaging demonstrates the moment at which Monalysin is inserted into the lipid membrane. These results collectively suggest that endogenous Monalysin is indeed a pore-forming toxin composed of a rigid structure before pore formation in the lipid membrane. The endogenous Monalysin characterized in this study could be a desirable tool for analyzing Drosophila’s immunity and the flies’ defense mechanisms against entomopathogenic bacteria.